Activation of Nociceptin/Orphanin FQ Peptide Receptors Disrupts Visual but Not Auditory Sensorimotor Gating in BALB/cByJ Mice: Comparison to Dopamine Receptor Agonists - Ces, Aurelia (Nature Publishing Group, 2012)
Nociceptin/orphanin FQ (N/OFQ) peptide and its receptor (NOP receptor) have been implicated in a host of brain functions and diseases, but the contribution of this neuropeptide system to behavioral processes of relevance to psychosis has not been investigated. We examined the effect of the NOP receptor antagonists, Compound 24 and J-113397, and the synthetic agonist, Ro64-6198, on time function (2–2000 ms prepulse–pulse intervals) of acoustic (80 dB/10 ms prepulse) and visual (1000 Lux/20 ms prepulse) prepulse inhibition of startle reflex (PPI), a preattentive sensory filtering mechanism that is central to perceptual and mental integration. The effects of the dopamine D1-like receptor agonist, SKF-81297, the D2-like receptor agonist, quinelorane, and the mixed D1/D2 agonist, apomorphine, were studied for comparison. When acoustic stimulus was used as prepulse, BALB/cByJ mice displayed a monotonic time function of PPI, and consistent with previous studies, apomorphine and SKF-81279 induced PPI impairment, whereas quinelorane had no effect. None of the NOP receptor ligands was effective on acoustic PPI. When flash light was used as prepulse, BALB/cByJ mice displayed a bell-shaped time function of PPI and all dopamine agonists were active. Ro64-6198 was also effective in reducing visual PPI. NOP receptor antagonists showed no activity but blocked disruptive effect of Ro64-6198. Finally, coadministration of the typical antipsychotic, haloperidol, attenuated PPI impairment induced by Ro64-6198, revealing involvement of a dopaminergic component. These findings show that pharmacological stimulation of NOP or dopamine D2-like receptors is more potent in disrupting visual than acoustic PPI in mice, whereas D1-like receptor activation disrupts both. They further suggest that dysfunction of N/OFQ transmission may be implicated in the pathogenesis of psychotic manifestations.